High genetic diversity of Babesia canis (Piana & Galli‐Valerio, 1895) in a recent local outbreak in Berlin/ Brandenburg, Germany. Issue 5 (25th June 2022) - Helm, Christina S.; Weingart, Christiane; Ramünke, Sabrina; Schäfer, Ingo; Müller, Elisabeth; von Samson‐Himmelstjerna, Georg; Kohn, Barbara; Krücken, Jürgen
Abstract: Canine babesiosis caused by Babesia canis (Piana & Galli‐Valerio, 1895) is emerging in new regions in Europe since its vector Dermacentor reticulatus (Fabricius, 1794) is expanding its geographic range. In the Berlin/Brandenburg area in northeast Germany, D. reticulatus is highly abundant but in the past only one autochthonous B. canis infection was reported. Since 2015, autochthonous cases were occasionally diagnosed but numbers increased since autumn 2019. The aim of the study was to genotype autochthonous canine Babesia spp. infections from Berlin/Brandenburg. Between 04/2015 and 01/2022, 46 dogs with acute babesiosis were presented to the small animal clinic (one dog was infected twice resulting in 47 samples). There were 32 dogs that had never left Berlin/Brandenburg and 14 others that had not left the region in the 6 weeks prior to disease onset. PCRs targeting the 18S rRNA and the Bc28.1 merozoite surface antigen were positive in 47 and 42 samples, respectively. Sequencing of cloned PCR products identified all samples as B. canis with 17 18S rRNA and 12 Bc28.1 haplotypes. Based on network analysis for 18S rRNA sequences and a previously described polymorphic dinucleotide, samples were assigned to two distinct clusters. One contained 31 and the other 16 samples. Using network analysis, the Bc28.1 haplotypes could also be separated into two clusters differing by at least five polymorphisms. Analyses of sequences from multiple clones indicated the presence of up to five 18S rRNA and eight Bc28.1 haplotypes and thus high parasite variability in an individual host. The genetic diversity could suggest that the parasites in the region have multiple origins, but diversity in individual dogs and dog populations from endemic regions is unknown. The suitability of both markers for genotyping is questionable due to potential intragenomic diversity for the rRNA and high intergenomic variability for the Bc28.1 marker.